“I WANTED TO BE PART OF NOT FORGETTING”: DIGITAL MEDIATION AND MEMORY IN POST-PANDEMIC TIMES - Moses, Adetobi (AoIR Selected Papers of Internet Research, 2026)
This paper investigates how Covid-19 digital archives may function as critical repositories for memory institutions and consequently lead to a better understanding of the role of digital technologies in mediating memory during future crisis events. To investigate this question, I utilized focus groups to understand how adults from a major American city responded to a selection of oral pandemic stories from Corona Diaries, a digital archive that was launched in March 2020. Findings suggest that engaging with the audio stories from the digital archive helped participants process their own pandemic experiences and reflect on the politicization of the pandemic. The content of the recordings also triggered new epiphanies among participants, helping them recalibrate their relationship to illness, loss, and memory. However, the personal dimensions of the digital archive at times fostered, and at other times challenged participants’ ability to connect to the stories, leading to competing opinions about the utility of digital archives. Overall, I argue that as memory culture becomes increasingly digitized and globalized, meaningful ways of concretizing local groups’ connections to traumatic disasters and crises must be prioritized within commemoration practices.